Estimation and comparative evaluation of tip and torque values of Saudis for bracket prescription - Ferdous Bukhary; Mohammed T. Bukhary; Sahar Albarakati (Saudi Dental Journal)
Objectives: The present study aimed at determining the tip and torque values of the teeth of Saudi adults with normal occlusion to develop orthodontic bracket prescription. In addition, we proposed to compare the results with published data of varied geographical distribution. Materials and Methods: The study sample consisted of 60 upper and lower study models of Saudi adults (30 males and 30 females) with normal occlusion and a balanced facial profile. Evaluated by experts, the torque and tip of teeth were measured using a torque angulation device. The collected data was analyzed using SPSS (IBM SPSS Inc., version 20, Chicago, IL, USA). The mean, and standard deviation were obtained for each measurement. Paired t-test, Independent t-test and student t-test were used for the comparison at a significant level of (p ≤ 0.05). Result: The results of torque and tip of teeth for the Saudi adult population showed no significant differences between the right and the left quadrants of the analyzed study sample. In general, there was no significant observed difference between male and female samples, accordingly, the Saudi tip and torque data were combined. However, the comparisons of the combined Saudi data to the published data showed significant differences (p ≤ 0.05). Conclusion: Statistically Significant differences were found between the combined Saudi data when compared to North American, Italian, African, Japanese, and Indian data. We inferred, that racial differences should be considered when presenting bracket prescriptions.